Türk Tarihinde Bir Sosyo-Kültürel Facia: Bektaşi Tekkelerinin Kapatilişi (Journal of Alevism-Bektashism Studies, 2013)
The most important period of the Bektashi order was in 1826. Also those years were the most resourceful period where the order can be adressed as a whole. Although the closure of Bektashi order was as a result of its spiritual connections with Janissary corps, it was explained with different reasons on documents. The government evaluated the subject in the context of religion and accused the order with faithless. This closure resulted in both cultural and economic losses in Anatolian and Rumelian Turkishness. Because this establishment was one of the forming orders of Turkish culture. Oral and written literature developed under the concept of unity of existence has a branch in this structure. The Bektashi order lived up to the present day with its prohibited ideas and influenced today’s ideas.